Stability of ascorbic acid, tocopherols and total folates in irradiated buckler sorrel leaves during refrigerated storage - Pinela, José (2018)
Ready-to-eat vegetables have become more popular in consumers’ market baskets due to their convenience and health benefits. The growth of this sector has promoted the introduction of new foods and the adoption of more efficient and eco-friendly postharvest technologies such as irradiation. However, a common consumer concern is whether irradiation adversely affects the nutritional value of food. In this sense, the suitability of post-packaging irradiation for preserving buckler sorrel (Rumex induratus Boiss. & Reut.) vitamins during refrigerated storage was evaluated. Buckler sorrel samples gathered in the Northeastern region of Portugal were hand-picked and a portion was immediately analyzed (fresh control). The remaining fresh material was packaged in polyethylene bags, irradiated at doses up to 6 kGy in a 60Co experimental chamber, and stored at 4 ºC for 12 d. A non-irradiated control followed the experiment. Ascorbic acid, tocopherols and total folates were analyzed by HPLC techniques. The four tocopherol isoforms were identified; α-tocopherol was the most abundant one in the fresh control, followed by γ-tocopherol. The treatment caused a decrease in the α-tocopherol levels, which was more marked with the consequent increase in dose. Interestingly, the non-irradiated stored control had the highest total tocopherol content (promoted especially by the γ isoform). In turn, ascorbic acid was more sensitive to irradiation than to storage time, while folates were only affected by the 2 kGy dose. Therefore, packaging and refrigeration were enough for the preservation of buckler sorrel vitamins for 12 d.